Performance of ESAT-6 for serodiagnosis of nonhuman primate tuberculosis: A meta-analysis - Min, Fangui; Wang, Jing; Zhang, Yu (Journal of Advanced Veterinary and Animal Research, 2015)
ESAT-6 is one of the most studied antigens in vaccine, diagnosis, and pathogenic mechanism of tuberculosis. In the present study, a meta-analysis was performed regarding the use of ESAT-6 based antibody detection test for diagnosing nonhuman primate (NHP) tuberculosis. Studies in English and Chinese were searched and selected strictly. Quality of included studies was assessed using the standardized QUADAS-2 tool. Heterogeneity was explored through meta-regression. Finally, eight studies were included with high degree of homogeneity. Quality of included studies was general satisfied except the bias of patient selection for the majority of serum samples were from experimental infections. Estimates of sensitivity ranged from 69% to 82%, while specificity ranged from 96% to 99%. Area under ROC curves and Q were 0.9503 and 0.8909 respectively, indicating a high diagnostic accuracy. Current evidence suggests that ESAT-6 based serodiagnosis has the potential to become useful diagnostic tools for NHP tuberculosis. http://dx.doi.org/10.5455/javar.2015.b58